METODE QUANTUM (Pengertian, Prosedur penggunaan dan keutamaannya) - Henny Sukmawati (Fakultas Agama Islam Universitas Islam Makassar (UIM), 2017)
Quantum Method is a method of learning that paved the way active participation of both parties to create a learning situation is pleasant, happy, motivating interest, for stimuli presented as well as beneficial for learners. The procedure for applying quantum learning model is a paradigm measures that must be adopted by students and teachers in learning activities. Learning is most effective when done in a pleasant atmosphere, environment and atmosphere that is not too formal, so that participants feel relaxed and relaxed. Lesson modules should not be complicated but should be presented in a simple and more into a real case. Learning strategies quantum learning and virtue is a strategy that is in use teachers who have a concept to be able to absorb the facts, concepts, procedures, and principles of a science with a quick, fun, and memorable.